CDK4/6 inhibitors: A focus on biomarkers of response and post-treatment therapeutic strategies in hormone receptor-positive HER2-negative breast cancer. (February 2021) - Migliaccio, Ilenia; Bonechi, Martina; McCartney, Amelia; Guarducci, Cristina; Benelli, Matteo; Biganzoli, Laura; Di Leo, Angelo; Malorni, Luca
Highlights: Resistance to CDK4/6 inhibitors is a clinical issue in metastatic breast cancer. Predictive biomarkers are eagerly awaited to personalize treatment strategies. Treatments after progression on CDK4/6 inhibitors are yet to be standardized. New strategies are being explored in ongoing clinical trials. Abstract: CDK4/6 inhibitors (CDK4/6i) in combination with endocrine therapy are the mainstay of treatment for patients with hormone receptor-positive, HER2 negative (HR+/HER2neg) metastatic breast cancer. However, resistance - either de novo or acquired - invariably occurs, leading to treatment failure and cancer progression. Genomic alterations, gene expression data and circulating biomarkers have been correlated to response to treatment, but to date no biomarker has been approved to stratify patients. Treatment strategies after progression on CDK4/6i are yet to be standardized. Current approaches include endocrine therapy alone or in combination with target therapy, or chemotherapy. New agents are in clinical development based on potential mechanisms of acquired resistance. Here we will review recent advancements in biomarkers of response to CDK4/6i, and in post- treatment therapeutic strategies.